Analysis of Elementary Students’ Interest in Football Learning in Jalancagak District - Moch. Reksha Arya Abdullah; Adang Sudrazat; Rizal Ahmad Fauzi (Journal Coaching Education Sports, 2026)
This study aimed to explore the factors influencing elementary students’ interest in football learning in Jalancagak District. A qualitative case study design was employed to gain an in-depth understanding of students’ experiences and perceptions toward football learning. Participants consisted of elementary students and physical education teachers selected through purposive sampling. Data were collected through semi-structured interviews, observations, and documentation, then analyzed using thematic analysis assisted by NVivo 12 software. The findings revealed that students’ interest in football learning was shaped by both internal and external factors. Internal factors included personal motivation and aspirations to become professional football players, while external factors involved family support, teacher roles, learning methods, facilities, and media exposure. Engaging practice-based learning, supportive teachers, and positive family encouragement significantly enhanced students’ enthusiasm and participation in football learning. However, limited facilities and inadequate infrastructure were identified as challenges affecting learning effectiveness. This study contributes to the literature by providing a contextual and qualitative understanding of how students construct interest in football learning within elementary school settings. The findings suggest the importance of adaptive learning strategies, supportive school environments, and improved facilities to foster students’ engagement in physical education.